The Relationship between Palestinian Student Teachers' Perception of Computer Technology and their Attitudes to Use it in Teaching - Khawla S. Sabri; Jamal M. Rabee (Sultan Qaboos University, 2014)
The objectives of the study were as follows: To examine the validity (or adequacy) of using the Technology Acceptance Model (TAM) with pre-service student teachers in the West Bank (Palestine), to identify the perceptions of student teachers with respect to ease and utility of using computer technology, and to identify the attitudes of student teachers toward computer technology and their intention to use it in teaching. To achieve these objectives, six null hypotheses were formulated. The sample consisted of 260 student teachers. A questionnaire was used to collect the data. The Structural Equation Modeling (SEM) technique was used to analyze data. Results revealed that the fit between the data TAM model was acceptable. Also, the results revealed that student teachers used computer technology with ease and this had a positive direct effect on their perception of its usefulness. In addition, perception of usefulness had a positive direct effect on the attitude of student teachers toward its use, which in turn, had a positive direct effect on their intention to use it. However, the perception of student teachers with respect to using computer technology with ease had no direct effect on their attitude toward its use, and their perception of usefulness of its use had no direct effect on their intention to use it.